Nano-non-woven fabric composite packaging material and preparation method thereof

Through nano-non-woven composite packaging materials, combined with polylactic acid, polybutylene terephthalate and nanomaterials, the shortcomings of existing packaging materials in moisture permeability, bacteriostatic and air conditioning functions are solved, and all-round protection of fruits is achieved, and the shelf life is extended.

CN119704834APending Publication Date: 2025-03-28SHAOXING BAILIJIE ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411913233.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing fruit fresh-preserving packaging materials have shortcomings in moisture permeability, antibacteriality and air conditioning functions, and it is difficult to comprehensively solve the various problems of fruit fresh-preserving.

Method used

The nano-non-woven composite packaging materials are used, including a non-woven layer, an air conditioning layer and a nanofilm layer. The air conditioning layer is composed of polylactic acid and polybutylene terephthalate, and the nanofilm layer contains amino modified nanotitanium dioxide and nanosilver.

Benefits of technology

The packaging material has excellent moisture permeability and antibacterial properties, which can regulate the atmosphere in the packaging, reduce the metabolic rate of fruits, extend the shelf life and reduce the risk of rot.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005206250360000051
    Figure BDA0005206250360000051
  • Figure BDA0005206250360000052
    Figure BDA0005206250360000052
  • Figure BDA0005206250360000061
    Figure BDA0005206250360000061
Patent Text Reader

Abstract

The invention relates to the technical field of packaging materials, and particularly discloses a nanometer-non-woven fabric composite packaging material and a preparation method thereof. The nanometer-non-woven fabric composite packaging material comprises a non-woven fabric layer, a modified atmosphere layer located on the surface of the non-woven fabric layer and a nanometer film layer located on the surface of the modified atmosphere layer. The modified atmosphere layer is prepared from the following components in parts by weight: 15 to 22 parts of polylactic acid, 20 to 30 parts of polybutylene terephthalate and 0.5 to 1.5 parts of compatilizer; a nano material used by the nano film layer comprises amino modified nano titanium dioxide and nano silver; on one hand, the composite packaging material provided by the invention has good antibacterial property and moisture permeability, on the other hand, the atmosphere in a packaging bag can be well adjusted through the appropriate ratio of the permeability of carbon dioxide to the permeability of oxygen, and when the composite packaging material is used for packaging fruits, the respiration rate of the fruits can be adjusted, the metabolism rate of the fruits can be reduced, and then the fresh-keeping period of the fruits is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of packaging materials, and in particular to a nano-nonwoven composite packaging material and a preparation method thereof. Background Art

[0002] As consumers' requirements for food safety and quality continue to increase, high-performance packaging materials have been widely used and developed in the field of food packaging, especially in the preservation of fruits. Although traditional plastic films have certain sealing and protective effects, they are obviously insufficient in terms of preservation effect and environmental performance. In recent years, the combination of nanotechnology and composite materials has brought new breakthroughs in food packaging, making packaging materials not only provide excellent air tightness and heat resistance, but also effectively extend the shelf life of food, which has a good application prospect.

[0003] At present, the common fruit preservation packaging materials on the market mainly include single-layer plastic film, coated paper and aluminum foil composite materials. Among them, single-layer plastic film is widely used because of its low cost, but its air permeability and moisture permeability are poor, and it is difficult to remove the water vapor in the package, which causes condensation on the surface of the fruit, creating conditions for the breeding and growth of mold, thus affecting the shelf life and shelf life of the fruit. Although coated paper has certain air permeability and moisture resistance, it is easy to lose its function under high temperature conditions, and its antibacterial properties are limited. It cannot effectively inhibit the growth of bacteria, causing the fruit to be easily contaminated by microorganisms and deteriorate. Aluminum foil composite materials have excellent barrier properties, but their opacity and high production costs limit their scope of application.

[0004] Therefore, it is particularly important to develop a new type of packaging material with good moisture permeability, antibacterial properties and atmosphere control function. Summary of the invention

[0005] In order to solve the various problems of existing packaging materials that cannot fully solve the preservation of fruits, the present application provides a nano-nonwoven composite packaging material and a preparation method thereof.

[0006] In a first aspect, the present application provides a nano-nonwoven composite packaging material, which adopts the following technical solution: A nano-nonwoven composite packaging material, comprising a nonwoven layer, an atmosphere-adjusting layer located on the surface of the nonwoven layer, and a nano-membrane layer located on the surface of the atmosphere-adjusting layer; The material used for the gas-adjusting layer includes the following components in parts by weight: 15-22 parts of polylactic acid, 20-30 parts of polybutylene terephthalate, and 0.5-1.5 parts of a compatibilizer; The nano materials used in the nano film layer include amino-modified nano titanium dioxide and nano silver.

[0007] The present application adopts non-woven fabric, polylactic acid, polybutylene terephthalate and nanomaterials to prepare a three-layer composite packaging material. The nano-non-woven composite packaging material can be used for fruit packaging, effectively maintain the freshness and humidity of the fruit, and significantly improve the preservation effect of the fruit. Specifically: the packaging material provided by the present application has a suitable ratio of carbon dioxide and oxygen permeability, which can well adjust the atmosphere in the packaging bag, match the breathing rate of the fruit itself to adjust the gas atmosphere concentration in the packaging, thereby effectively reducing the respiration of the fruit and reducing the metabolism rate of the fruit; on the other hand, it has excellent moisture permeability and antibacterial properties. When used for fruit packaging, it can discharge the water vapor caused by the respiration of the fruit in the packaging to the outside of the packaging, avoid the contact with condensed water during the fruit preservation process and cause bacterial growth, and at the same time adjust the humidity and gas concentration of the environment in the packaging, effectively extend the fruit shelf life, and increase the shelf life of the fruit. Among them, the non-woven fabric layer, as the basic support, not only has good mechanical properties, but also provides hygroscopicity, which helps to maintain the freshness and moisture of the fruit. The atmosphere-adjusting layer is composed of polylactic acid and polybutylene terephthalate, which have good air permeability and can adjust the permeability of oxygen and carbon dioxide and the respiration rate of fruits. The amino-modified nano-titanium dioxide and nano-silver in the nano-film layer give the packaging material excellent antibacterial and antifungal properties, which can effectively inhibit the growth of bacteria and mold and reduce the risk of fruit rot; in addition, the nano-titanium dioxide particles can also adsorb and decompose the ethylene gas produced during the storage of fruits, delay the ripening speed of fruits, and keep the fruits fresh. Combining the above technical means, the nano-nonwoven composite packaging material not only has good moisture permeability and air permeability, but also has excellent moisturizing and antibacterial effects, which can protect fruits in all directions and ensure their quality during long-term transportation and storage.

[0008] Optionally, the material used for the atmosphere-adjusting layer includes the following components in parts by weight: 18-20 parts of polylactic acid, 23-27 parts of polybutylene terephthalate, and 0.5-1.5 parts of a compatibilizer.

[0009] Optionally, the formation process of the gas-conditioning layer is: polylactic acid, polybutylene terephthalate and a compatibilizer are mixed, and then melt-blended and blown into a film to obtain a gas-conditioning film; and then the gas-conditioning film is placed on the surface of a non-woven fabric, and hot-pressed at 150-170° C. to form the gas-conditioning layer.

[0010] Optionally, the formation process of the nano film layer is: the nano material is made into a nano sol, which is then quickly coated on the surface of the gas conditioning layer, and vacuum dried at 70-80° C. to form the nano film layer.

[0011] Optionally, the coating amount of the nanosol is 150-200 g / m 2 .

[0012] In some embodiments, the coating amount of the nanosol can be 150-165 g / m 2 150-175g / m 2 150-185g / m 2 150-200g / m 2 165-175g / m 2 165-185g / m 2 165-200g / m 2 175-185g / m 2 175-200g / m 2 or 185-200g / m 2 .

[0013] In a specific embodiment, the coating amount of the nanosol can be 150g / m 2 , 165g / m 2 , 175g / m 2 , 185g / m 2 or 200g / m 2 .

[0014] Optionally, the coating amount of the nanosol is 165-185g / m 2 .

[0015] In this application, the coating amount of the nanosol will affect the antibacterial effect of the nano-nonwoven composite packaging material. Through experimental research, it was found that by further controlling the coating amount of the nanosol within the above range, the antibacterial rate of the prepared nano-nonwoven composite packaging material against Escherichia coli and Staphylococcus aureus can reach more than 98.0%.

[0016] Optionally, the compatibilizer is AX8900.

[0017] Optionally, the water vapor permeability of the nano-nonwoven composite packaging material is 4011-4556 g / m 2 24h, The ratio of CO2 / O2 transmittance is (2.1-2.8):1.

[0018] In the present application, when the CO2 / O2 permeability ratio is too small, the aerobic respiration of the fruit will be enhanced, resulting in excessive consumption of organic matter in the fruit, accelerating the deterioration of the fruit; when the CO2 / O2 permeability ratio is too large, the anaerobic respiration of the fruit will be aggravated, which will easily cause the fruit to rot. The inventors of the present application have found that by controlling the CO2 / O2 permeability ratio of the nano-nonwoven composite packaging material within the above range, the CO2 / O2 permeability ratio of the packaging material can inhibit the respiration of the fruit, reduce its metabolic rate, and thus extend its shelf life, achieving a good preservation effect.

[0019] In the second aspect, the present application provides a method for preparing a nano-non-woven composite packaging material, comprising the following steps: first, mixing the materials of each gas-conditioning layer, and then melt-blending and blow-molding them into a film to obtain a gas-conditioning film; then placing the gas-conditioning film on the surface of the non-woven fabric, and hot-pressing it at 150-170°C to form a gas-conditioning layer; then making the nanomaterial into a sol, and then quickly coating it on the surface of the gas-conditioning layer, and vacuum drying it at 70-80°C to obtain a nano-non-woven composite packaging material.

[0020] In summary, this application has the following beneficial effects: 1. The present application uses non-woven fabric as a base material, polylactic acid and polybutylene terephthalate as materials for the gas-adjusting layer, and amino-modified nano-titanium dioxide and other nano-materials as surface materials, thereby preparing a nano-non-woven fabric composite packaging material with good moisture permeability and antibacterial properties and gas-adjusting function. The nano-non-woven fabric composite packaging material is used for fruit packaging, which can well regulate the atmosphere in the packaging bag, regulate the metabolic rate of the fruit, and thus effectively extend the shelf life of the fruit.

[0021] 2. The nano-nonwoven composite packaging material provided in the present application also has excellent moisture permeability and antibacterial properties, and can discharge the water vapor caused by the respiration of the fruit inside the package to the outside of the package, avoiding the growth of bacteria caused by the contact with condensed water during the fruit preservation process, and effectively extending the shelf life of the fruit.

[0022] 2. The present application further controls the weight of each component of the material used in the atmosphere-adjusting layer within the following range: 18-20 parts of polylactic acid, 23-27 parts of polybutylene terephthalate, and 0.5-1.5 parts of a compatibilizer. The CO2 / O2 permeability ratio of the obtained nano-nonwoven composite packaging material is (25-2.6): 1. The above CO2 / O2 permeability ratio has a better inhibitory effect on the respiration of fruits and can make the preservation effect of fruits more lasting.

[0023] 3. The present application further controls the coating amount of the nanosol to 165-185 g / m 2 Within the range, the antibacterial rates of the prepared nano-nonwoven composite packaging material on Escherichia coli and Staphylococcus aureus can reach more than 98.0% at a relatively low cost. DETAILED DESCRIPTION

[0024] The present application provides a nano-nonwoven composite packaging material, comprising a nonwoven layer, an air conditioning layer located on the surface of the nonwoven layer, and a nano film layer located on the surface of the air conditioning layer; the material used in the air conditioning layer comprises the following components in parts by weight: 15-22 parts of polylactic acid, 20-30 parts of polybutylene terephthalate, and 0.5-1.5 parts of a compatibilizer; the nano material used in the nano film layer comprises amino-modified nano titanium dioxide and nano silver. Among them, the material used in the air conditioning layer comprises the following components in parts by weight: 18-20 parts of polylactic acid, 23-27 parts of polybutylene terephthalate, and 0.5-1.5 parts of a compatibilizer.

[0025] The method for preparing the above-mentioned nano-nonwoven composite packaging material comprises the following steps: (1) Polylactic acid, polybutylene terephthalate and a compatibilizer are mixed and added into a twin-screw extruder for melt blending, and then blown into a film by a single-screw blow molding machine at a film blowing temperature of 170-190° C. to obtain a gas-conditioned film, which is placed on a non-woven fabric surface and hot-pressed at 150-170° C. to form a gas-conditioned layer.

[0026] (2) Add silane coupling agent KH550 to 95% ethanol, stir evenly and heat to 75°C, and react for 1 hour; then add nano-titanium dioxide, ultrasonically disperse, and stir to react for 2 hours; wash with ethanol three times, filter, and dry in a vacuum drying oven at 60°C for 5 hours to obtain amino-modified nano-titanium dioxide particles; wherein the mass ratio of the silane coupling agent KH550, nano-titanium dioxide and 95% ethanol is 1:(1.5-2):(10-15).

[0027] (3) Dissolve 1 g of polyvinyl pyrrolidone in 100 g of anhydrous ethanol, add 5 g of amino-modified nano titanium dioxide particles and 2 g of nano silver particles, stir until uniformly dispersed, then add 35 g of tetrabutyl titanate, stir evenly, and obtain solution I; adjust 50% ethanol to a pH of 4.0 with 25% hydrochloric acid solution to obtain solution II; under stirring, add solution II dropwise into solution I, the volume ratio of solution II to solution I being 1:(15-20), to form a nanosol.

[0028] (4) The nanosol is quickly coated on the surface of the gas conditioning layer formed in step (1), and the coating amount of the nanosol is 150-200g / m 2 , and vacuum dried at 70-80°C for 6-10h to obtain a nano-nonwoven composite packaging material.

[0029] In the present application, the model of non-woven fabric is PET antibacterial non-woven fabric, purchased from Shanghai Langyi Functional Materials Co., Ltd.; the CAS number of polylactic acid is 26680-10-4, purchased from Merck; polybutylene terephthalate is purchased from McLean; the brand of compatibilizer is AX8900, purchased from Shanghai Jianbang Industrial Co., Ltd.; the particle size of nano-titanium dioxide is 30nm, purchased from Ningbo Jiwei Nano New Materials Technology Co., Ltd.; the particle size of nano-silver is 50nm, purchased from Nanjing Donna Biotechnology Co., Ltd.; the raw materials, reagents, solvents, etc. used in this application can all be obtained commercially.

[0030] The present application is further described in detail below in combination with preparation examples, embodiments, and performance testing experiments.

[0031] Preparation Example 1 Preparation Example 1 provides an amino-modified nano titanium dioxide particle.

[0032] The preparation method of the amino-modified nano titanium dioxide particles comprises the following steps: adding 10 g of silane coupling agent KH550 to 150 g of 95% ethanol, stirring evenly and heating to 75° C., and reacting for 1 hour; then adding 15 g of nano titanium dioxide, ultrasonically dispersing, and stirring for 2 hours; washing with ethanol for 3 times, filtering, and drying in a vacuum drying oven at 60° C. for 5 hours to obtain amino-modified nano titanium dioxide particles; Examples 1-8 Examples 1-8 each provide a nano-nonwoven composite packaging material.

[0033] The difference between the above embodiments lies in the addition amount of each component in the gas-adjusting layer material.

[0034] The method for preparing the nano-nonwoven composite packaging material provided in Examples 1-8 comprises the following steps: (1) Polylactic acid, polybutylene terephthalate and 1 g of a compatibilizer were mixed and added into a twin-screw extruder for melt blending. The mixture was then blown into a film using a single-screw blow molding machine at a film blowing temperature of 190° C. to obtain a gas-conditioned film with a thickness of 0.1 mm. The gas-conditioned film was placed on a non-woven fabric surface and hot-pressed at 160° C. to form a gas-conditioned layer.

[0035] (2) Prepare amino-modified nano titanium dioxide particles according to the method of Preparation Example 1.

[0036] (3) dissolving 1 g of polyvinyl pyrrolidone in 100 g of anhydrous ethanol, adding 5 g of amino-modified nano titanium dioxide particles and 2 g of nano silver particles, stirring until uniformly dispersed, and then adding 35 g of tetrabutyl titanate, stirring evenly to obtain solution I; adjusting 50% ethanol to a pH of 4.0 with 25% hydrochloric acid solution to obtain solution II; while stirring, adding solution II dropwise into solution I, the volume ratio of solution II to solution I being 1:15, to form a nanosol; (4) The nanosol is quickly coated on the surface of the gas conditioning layer formed in step (1). The coating amount of the nanosol is 175 g / m 2 , and dried in vacuum at 75°C for 8 h to obtain a nano-nonwoven composite packaging material.

[0037] Table 1 Addition amount of each component in the gas-adjusting layer material of Examples 1-8 Examples 9-12 Examples 9-12 each provide a nano-nonwoven composite packaging material.

[0038] The difference between the above embodiment and embodiment 2 is that the coating amount of the nanosol in step (4) is specifically shown in Table 2 below.

[0039] Table 2 Coating amount of nanosol in Examples 9-12 Comparative Example 1 Comparative Example 1 provides a nano-nonwoven composite packaging material.

[0040] The difference between the comparative example and Example 2 is that the amino-modified nano-titanium dioxide is replaced by nano-titanium dioxide.

[0041] Comparative Example 2 Comparative Example 2 provides a nano-nonwoven composite packaging material.

[0042] The difference between the comparative example and Example 2 is that the amount of polybutylene terephthalate added in step (2) is 0 g.

[0043] Comparative Example 3 Comparative Example 3 provides a nano-nonwoven composite packaging material.

[0044] The difference between the comparative example and Example 2 is that the amount of polybutylene terephthalate added in step (2) is 10 g.

[0045] Performance testing The performance of the nano-nonwoven composite packaging materials provided in Examples 1-12 and Comparative Examples 1-3 was tested, and the results are shown in Table 3 below.

[0046] (1) Water vapor transmission rate: Referring to GB / T21529-2008, the water vapor transmission rate of composite packaging materials was tested using an OGT-G3 electrolytic water vapor transmission meter.

[0047] (2) CO2 / O2 permeability ratio: The CO2 permeability and O2 permeability of the packaging material are measured separately, and then the CO2 / O2 permeability ratio is calculated according to the following formula: CO2 / O2 transmittance ratio = CO2 transmittance / O2 transmittance × 100% Among them, CO2 permeability and O2 permeability are both tested by thin film pressure difference method gas permeometer GTR-721, and the testing method refers to GB 1038.

[0048] (3) Antibacterial performance test: Refer to GB / T 31402-2015 "Test method for antibacterial performance of plastic surfaces" to test the antibacterial effect of composite packaging materials on Escherichia coli ATCC8739 and Staphylococcus aureus ATCC6538. Repeat the test for 5 samples of each composite packaging material and take the average value. Table 3 Performance test results of composite packaging materials of Examples 1-12 and Comparative Examples 1-3 According to the test results in Table 3, the water vapor permeability of the composite packaging materials prepared in Examples 1-12 is 4011-4556 g / m 2 ·24h, CO2 / O2 transmission ratio is (2.1-2.8): 1, Escherichia coli inhibition rate is 97.3-98.9%, Staphylococcus aureus inhibition rate is 97.8-99.1%; while the Escherichia coli inhibition rate of the composite packaging material obtained in comparative example 1 is only 90.6%, and the Staphylococcus aureus inhibition rate is only 86.4%; the water vapor transmission rate of the composite packaging material obtained in comparative examples 2-3 is only 3038-362g / m 2 ·24h, the ratio of CO2 / O2 permeability is only (1.5-1.8): 1. Therefore, it is explained that the present application uses non-woven fabric as the base material, polylactic acid and polybutylene terephthalate as the material of the gas-adjusting layer, and amino-modified nano titanium dioxide and other nanomaterials as the surface material. The prepared nano-non-woven fabric composite packaging material has good moisture permeability and antibacterial properties, and a suitable ratio of CO2 / O2 permeability. It is used for fruit packaging to adjust the moisture content and the carbon dioxide and oxygen atmosphere in the package, thereby extending the shelf life of the fruit.

[0049] The test results of Examples 1-8 show that the water vapor permeability of the composite packaging materials obtained in Examples 2-3 and 6-7 is 4278-4432 g / m 2 24h (≥4200g / m 2 ·24h), the CO2 / O2 permeability ratio is 2.5-2.6; while the CO2 / O2 permeability ratio of the composite packaging material obtained in Example 1 is 2.8:1, and the water vapor permeability of the composite packaging materials obtained in Examples 4-5 and 8 is 4011-4169g / m 2 24h(<4200g / m 2 ·24h). Therefore, it is explained that the present application further controls the weight of each component of the material used in the atmosphere-adjusting layer within the following range: 18-20 parts of polylactic acid, 23-27 parts of polybutylene terephthalate, and 0.5-1.5 parts of compatibilizer, and the obtained nano-nonwoven composite packaging material has better moisture permeability, a more suitable CO2 / O2 permeability ratio, and a more lasting preservation effect on fruits.

[0050] From the test results of Example 3 and Examples 9-12, it can be seen that with the increase in the coating amount of nanosol, the water vapor permeability of the obtained nano-nonwoven composite packaging material shows a gradually decreasing trend, the CO2 / O2 permeability ratio remains basically unchanged, and the antibacterial rates of Escherichia coli and Staphylococcus aureus both show a trend of first increasing and then remaining basically unchanged. Further comparison found that the antibacterial rate of Escherichia coli of the nano-nonwoven composite packaging material obtained in Examples 3 and Examples 10-12 was 98.1-98.7% (≥98.0%), and the antibacterial rate of Staphylococcus aureus was 98.4-99.1% (≥98.0%). Therefore, considering the comprehensive cost, the present application further controls the coating amount of nanosol to 165-185g / m 2 Within this range, nano-nonwoven composite packaging materials with good moisture permeability and excellent antibacterial properties can be obtained at a lower cost.

[0051] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A nano-nonwoven composite packaging material, characterized in that: It includes a non-woven fabric layer, an air conditioning layer located on the surface of the non-woven fabric layer, and a nano-membrane layer located on the surface of the air conditioning layer; The material used for the gas-adjusting layer includes the following components in parts by weight: 15-22 parts of polylactic acid, 20-30 parts of polybutylene terephthalate, and 0.5-1.5 parts of a compatibilizer; The nano materials used in the nano film layer include amino-modified nano titanium dioxide and nano silver.

2. The nano-nonwoven composite packaging material according to claim 1, characterized in that: The material used for the gas-adjusting layer includes the following components in parts by weight: 18-20 parts of polylactic acid, 23-27 parts of polybutylene terephthalate, and 0.5-1.5 parts of a compatibilizer.

3. The nano-nonwoven composite packaging material according to claim 1, characterized in that: The formation process of the gas-adjusting layer is as follows: polylactic acid, polybutylene terephthalate and a compatibilizer are mixed, then melt-blended and blown into a film to obtain a gas-adjusting film; the gas-adjusting film is then placed on the surface of a non-woven fabric, and hot-pressed at 150-170° C. to form the gas-adjusting layer.

4. The nano-nonwoven composite packaging material according to claim 3, characterized in that: The formation process of the nano film layer is as follows: the nano material is made into a nano sol, which is then quickly coated on the surface of the gas conditioning layer, and vacuum dried at 70-80° C. to form the nano film layer.

5. The nano-nonwoven composite packaging material according to claim 1, characterized in that: The coating amount of the nanosol is 150-200g / m 2 .

6. The nano-nonwoven composite packaging material according to claim 1, characterized in that: The coating amount of the nanosol is 165-185g / m 2 .

7. The nano-nonwoven composite packaging material according to claim 1, characterized in that: The compatibilizer is AX8900.

8. The nano-nonwoven composite packaging material according to any one of claims 1 to 7, characterized in that: The water vapor permeability of the nano-nonwoven composite packaging material is 4011-4556 g / m 2 ·24h, the ratio of CO2 / O2 transmission rate is (2.1-2.8):

1.

9. The method for preparing the nano-nonwoven composite packaging material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Firstly, various materials of the atmosphere-adjusting layer are mixed, and then melt-blended and blown into a film to obtain an atmosphere-adjusting film; The modified atmosphere film is then placed on the surface of the non-woven fabric and hot-pressed at 150-170°C to form a modified atmosphere layer; the nanomaterial is then made into a sol and then quickly coated on the surface of the modified atmosphere layer and vacuum dried at 70-80°C to obtain a nano-non-woven fabric composite packaging material.

Citation Information

Patent Citations

  • Method for manufacturing nano-coating with microwave absorbing and radiation functions

    CN103044981A

  • Preparation method of nanometer titanium dioxide composite nanometer silver sol

    CN104824020A

  • Preparation method of biodegradable modified atmosphere film for fresh keeping of edible mushrooms

    CN113278270A

  • High-performance antibacterial ceramic coating and preparation process thereof

    CN115011249A

  • Nano antibacterial air filtering hot air non-woven fabric and preparation method thereof

    CN116001404A